A wolf by the ears - Karlin, Wayne (University of Massachusetts Press, 2020)
"During the War of 1812, thousands of enslaved people from plantations across the Tidewater rallied to the British side, turning against an American republic that had barred them from the promises of freedom and democracy. Set against the backdrop of rebellion and war, Wayne Karlin's A Wolf by the Ears follows the interconnected stories of Towerhill and Sarai, two African slaves, and their master, Jacob Hallam. Educated side-by-side and inseparable as children, the three come of age as they are forced to grapple with-and break free of-the fraught linkage of black and white Americans and how differently each defined what it means to fight for freedom. Sarai and Jacob are caught in the tension between the dream of equality, the reality of slavery, and their own hearts, while Towerhill sits at the head of a company of black marines that is part of the force that takes Washington and watches the White House burn"--